The clock struck one : a time-telling tale - Harris, Trudy, 1949- (Millbrook Press, 2009)
Rhyming text expands on the nursery rhyme, "Hickory Dickory Dock," as a cat chases the mouse up the clock, followed by other animals, until midnight arrives and the tired creatures fall asleep. Includes facts about clocks and basic information about telling time.